A Grounded Theory Approach to Understanding Jombang Government Strategy in Facing the Era of Digitalization - Khumairoh, Devy Riesta Zuhrotul; Nukyanto, Damainsa Prahesti (Jejaring Administrasi Publik, 2024)
In 1967, Glaser and Strauss created a book entitled "The Discovery of Grounded Theory; Strategies for Qualitative Research'', which was published and became a breakthrough in qualitative research. The work offers systematic consensus methodologies and strategies for a wide range of qualitative research practices. When talking about public administration, grounded theory is rarely used in literature studies, especially in Indonesia. In public administration, grounded theory methodology can be directed toward understanding how the government develops strategic processes for policy, both at the organizational and individual levels. This article discusses the grounded theory research method approach, which is aimed at understanding how the Jombang Regency Regional Government develops strategic processes in facing the era of digitalization. In-depth interviews were conducted with 10 high-ranking regional government officials. This is intended to understand in depth their understanding and experience in managing changing situations. The research results show that there are five core categories: (1) human resource development; (2) technological innovation; (3) improving the management system; (4) security; and (5) mindset. By using selective and axial coding, it was found that there were two main functions of strategy that emerged, namely (1) system maintenance; and (2) adaptation to global change. Keywords: Grounded Theory, Public Administration, Public Policy, Strategy